The association between caffeine intake and mental health status among undergraduate medical student in Health Campus Of Universiti Sains Malaysia, Kelantan - Najisi, Ika Rafiena Muhamad (Universiti Sains Malaysia, 2024)
Caffeine is a widely consumed psychoactive substance, commonly used to enhance alertness and performance, especially among students. The consumption patterns and potential impacts of caffeine on mental health among medical students, who are often under significant academic and psychological stress, are not well understood. This study aimed to explore the association between caffeine intake and mental health status among undergraduate medical students at the Health Campus of Universiti Sains Malaysia Kelantan. This was a cross-sectional study that involved a sample of undergraduate medical students from the Health Campus of Universiti Sains Malaysia Kelantan. Data on caffeine intake and mental health status were collected through a self-administered questionnaire. Mental health status was assessed using the Generalized Anxiety Disorder 7 (GAD-7) scale for anxiety and the Patient Health Questionnaire 9 (PHQ-9) for depression. SPSS version 27.0 was used to analyse the data. Based on the study finding, 64.1% of the student consumed caffeine, while 35.9% of the student did not consume caffeine. There was no significant association between caffeine status and mental health scoring of GAD-7 (p = 0.478) and PHQ-9 (p = 0.820). The study concluded that there was no significant association between caffeine intake and mental health status, as measured by GAD-7 and PHQ-9 scores, among undergraduate medical students at the Health Campus of Universiti Sains Malaysia Kelantan. These results indicate that caffeine consumption might not be a major contributing factor to the mental health outcomes in this population. Other factors such as academic stress, cultural influences, smoking habits, economic conditions, and mental health history were not directly examined in this study. Further research is needed to explore other potential factors affecting the mental health of medical students and to understand the broader implications of caffeine consumption.